2020
DOI: 10.1590/2318-0889202032e200032
|View full text |Cite
|
Sign up to set email alerts
|

Scientific production of women in Brazil

Abstract: Researchers concentrate their efforts to understand the different female relations with science, using approaches that review their scientific and technological participation, as well as, seeking to understand their academic trajectory and performance. In this context, this study aimed to analyze the participation of women using as database the set of PhD graduates who have their curricula entered in the Lattes Platform. The data were collected and selected obtaining a set of 125,515 curricula of women who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…On the other hand, the impact of Brazilian research is lower for Social and Human Sciences (McManus et al 2020), which is confirmed by the low representation of Brazilians for these fields in the Ioannidis et al (2020) ranks. A recent analysis by Santiago et al (2020) showed significant disparities in the number of women holding a Ph.D. between areas in Brazil, with a predominance in the Humanities (19.8% of women Ph.D.), and a very small presence in Engineering (4.3%). In contrast, the number of female Brazilian scientists present in the ranks analyzed here does not reflect this pattern, since the lowest representation observed was in the Economic & Social Science and Arts & Humanities domains.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the impact of Brazilian research is lower for Social and Human Sciences (McManus et al 2020), which is confirmed by the low representation of Brazilians for these fields in the Ioannidis et al (2020) ranks. A recent analysis by Santiago et al (2020) showed significant disparities in the number of women holding a Ph.D. between areas in Brazil, with a predominance in the Humanities (19.8% of women Ph.D.), and a very small presence in Engineering (4.3%). In contrast, the number of female Brazilian scientists present in the ranks analyzed here does not reflect this pattern, since the lowest representation observed was in the Economic & Social Science and Arts & Humanities domains.…”
Section: Discussionmentioning
confidence: 99%
“…La vinculación de estos estudios con la bibliometría, comenzó por el interés de conocer cuál era el rol de la mujer dentro de la ciencia; las diferencias entre hombres y mujeres en la producción científica; su desarrollo y evolución a través del tiempo y sus diferencias en cuanto a nacionalidades (Sánchez Jasso, Rivera Gómez, & Velasco Orozco, 2016). Se encontraron investigaciones donde se refleja la presencia femenina en la investigación dentro de ramas específicas del conocimiento (Santiago, Alfonso, & Días, 2020) o para marcar la diferencia entre ambos géneros en aspectos como la productividad (Sebo, de Lucía, & Vernaz, 2021), el impacto y el índice de citas (Chan & Torgler, 2020) y la colaboración entre investigadores en una institución, país, campo de investigación o colección documental (Paswan & Singh, 2020).…”
Section: Aportaciones Españolas Y Portuguesas a La Iconference 2023unclassified
“…With the development of extractors, it was possible to use Lattes Database to draw a bigger picture of the Brazilian Innovation System. Examples are snapshots of the scientific production (Dias and Moita, 2018), scientific regional distribution (Sidone, Haddad and Mena-Chalco, 2016;, knowledge field particularities (Arruda et al, 2009;Hilário and Grácio, 2017;McManus and Neves, 2020), scientific collaboration and coauthorship networks (Fonseca, Fernandes and Fonseca, 2017;Mena-Chalco et al, 2014), gender inequality in scientific areas (Oliveira, Mello and Rigolin, 2020;Perlin et al, 2017;Santiago, Affonso and Dias, 2020), academic genealogy studies (Damaceno et al, and Mena-Chalco, 2018), and other scientometric and network analysis such as the research output in response to the Zika Crisis (Sampaio et al, 2020) and tuberculosis , development of methods to assess researcher quality-oriented to specific purposes (Duarte, Weber and Pacheco, 2018), trust analysis in cooperation in research (Adamatti and Castelfranchi, 2015) and predatory publishing (Perlin, Imasato and Borenstein, 2018).…”
Section: Lattes Curricula Cv-lattesmentioning
confidence: 99%